Survey on DDoS defense mechanisms. (7th January 2019) - Fenil, E.; Mohan Kumar, P.
Summary: It is a prominent attack used by the attackers to cripple an online service. The method of implementation can either be from a single source or a list of common users (zombie army) who are modulated from the command centers. Hence, in the latter case, they are called denial‐of‐service attacks. A substantial amount of distributed users has malware software that turns all these systems into bots without the user's consent. This aspect adds more to the complexity of detecting the attacker who is well masqueraded. These serve as a severe problem for Internet services and the network. It is mandatory to distinguish between a legitimate and a malicious user. There are many defense mechanisms that combat these types of attacks. This presentation mainly highlights the details of denial‐of‐service attacks and their various mechanisms and types and compares studies on different mechanisms that have been proposed. Finally, this gives an insight into future prospects in the research field for secured Internet services.